x → 0 lim x ln ( x + 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We first substitute x = 0
x → 0 lim x ln ( x + 1 ) = 0 0
We get a 0 0 situation, so we can apply L’H o ˆ pital’s rule.
We differentiate both numerator and denominator to get:
x → 0 lim x ln ( x + 1 ) = d x d ( x ) d x d ( ln ( x + 1 ) ) = x + 1 1
Now we can substitute x = 0 and get the answer.
x → 0 lim x ln ( x + 1 ) = 0 + 1 1 = 1
Pun: There is a LIMIT to the amount of limit puns that i can come up with.
Uff, again l hopital.
Log in to reply
I don't like other methods, they are long :(
Log in to reply
You should do those long, rigorous methods.
@Kriti Kamal , which method you used? I would love to know!
Log in to reply
I am posting it.
Log in to reply
@A Former Brilliant Member – Why did you delete it?
How you do know that the limit of the differentials is the same?
If i take the exponential of top and bottom I get (x +1)/e^x
e^x limits to 1 as x goes to 0
x + 1 limits to 1 as x goes to 0
so this approach gets the answer of 1.
Is this also valid ?
Log in to reply
Read this wiki on L'Hopital's Rule . It explains why it works for the certain situations
How is ln ( 0 + 1 ) = 0 ???
So as you can see, putting x=0 does not help, you become sick, so you need to go to the Hospital. Idk what pun to use.
Stop calling "L'Hôpital" Hospital!!!!!!!
Log in to reply
That was the best or weird pun which would be punny(funny) I could think of.
Log in to reply
How can a person's name be "Hospital"?
Log in to reply
@Vinayak Srivastava – How can a person's surname in India be 'Papadwala','Dabbawala'.
Log in to reply
@Siddharth Chakravarty – Let it be! :)
Log in to reply
@Vinayak Srivastava – Btw, what is your pun approach? :D
Log in to reply
@Siddharth Chakravarty – I didn't get anything good, so I wrote this title. :)
@Siddharth Chakravarty , 😂 you gave me the reason to use l hopital method.
Let f ( x ) = ln x
Then f ′ ( x ) = x 1
So, f ′ ( 1 ) = 1 1 = 1 =
x → 0 lim x ln ( 1 + x ) − ln 1
= x → 0 lim x ln ( 1 + x )
Are you Alak Bhattacharya Sir?
Log in to reply
Yes, @Foolish Learner has exact same profile as Mr. Alak @Vinayak Srivastava , but I don't know why he changed to "mention[6594224:Foolish Learner]" even though he is a "very smart learner".
Problem Loading...
Note Loading...
Set Loading...
Usually L'Hopital's Rule is the way i would go, but i decided to take a different route.
The Taylor Seriers expansion of ln ( x + 1 ) at x = 0 is n = 0 ∑ ∞ ( − 1 ) n + 1 n x n = x − 2 x 2 + 3 x 3 − 4 x 4 + …
We can plug this into our limit and we can see that: x → 0 lim x ln ( x + 1 ) ⟹ x → 0 lim x x − 2 x 2 + 3 x 3 − 4 x 4 + … = x → 0 lim 1 − 2 x + 3 x 2 − 4 x 3 + … = 1 − 2 0 + 3 0 2 − 4 0 3 + ⋯ = 1